2018
DOI: 10.2147/btt.s150958
|View full text |Cite
|
Sign up to set email alerts
|

The conundrum of indeterminate QuantiFERON-TB Gold results before anti-tumor necrosis factor initiation

Abstract: BackgroundTumor necrosis factor alpha (TNFα) is a key cytokine in both the pathogenesis of inflammatory bowel disease (IBD) and rheumatoid arthritis (RA) and the host defense against tuberculosis (TB). Consequently, anti-TNFα medications result in an increased risk of latent TB infection (LTBI) reactivation. Here, we sought to evaluate the factors affecting the results of QuantiFERON-TB Gold In-Tube (QFT-GIT) assay as a screening tool for LTBI.MethodsWe conducted an observational, retrospective study in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…All but one of the indeterminate QuantiFERON ® results were due to an inadequate immune response, suggesting that it is the immunosuppressive therapy leading to the indeterminate results rather than the acute flare itself. These findings are in keeping with other key studies [ 13 , 14 ]. In our centre, QuantiFERON ® TB Gold In-Tube takes, on average, 2–3 days to return a result; therefore, it can result in significant treatment delays.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…All but one of the indeterminate QuantiFERON ® results were due to an inadequate immune response, suggesting that it is the immunosuppressive therapy leading to the indeterminate results rather than the acute flare itself. These findings are in keeping with other key studies [ 13 , 14 ]. In our centre, QuantiFERON ® TB Gold In-Tube takes, on average, 2–3 days to return a result; therefore, it can result in significant treatment delays.…”
Section: Discussionsupporting
confidence: 93%
“…In the general population, studies show rates of indeterminate results of 3.8% (8). However, two separate studies in populations with IBD, who were tested prior to initiation of anti-TNFα, showed indeterminate results in 19.5% and 22% of the population [ 13 , 14 ], where authors found corticosteroid use and hospitalization were risk factors associated with an indeterminate result.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the QFT-Plus assay includes a mitogen-based control designed to nonspecifically elicit a T-cell response and thus infer the immunological fitness of the studied individuals. It is well known that active inflammation or immunosuppressive drug use is associated with QFT-Plus indeterminate results [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…27 The results indicate that TB infection may be more difficult to detect in this group compared to other groups. 31,32 Many studies have revealed that high SLEDAI scores are related to more severe symptoms, poor haematology and immunology features and a high probability of indeterminate results. 30,33 Similarly, our study revealed that, compared with other groups, the active group has the lowest IFN-γ level, which reflects an abnormality of the immune response.…”
Section: Discussionmentioning
confidence: 99%